Microbiological Evaluation of Opened Saline Bottles for Scleral Lens Use and Hygiene Habits of Scleral Lens Patients. Issue 3 (March 2021) - Jeong, Moon; Lee, Karen L.; She, Rosemary C.; Chiu, Gloria B.
Abstract : SIGNIFICANCE: Scleral lenses have become a widely used treatment option for patients with irregular corneas and ocular surface disease. Successful wear entails use of a nonpreserved saline solution to fill the lens before application on the eye. PURPOSE: The purposes of this study were to evaluate solution from opened bottles of multidose preservative-free saline for microbiological growth and to better understand study participant hygiene habits while handling these bottles for scleral lens wear. METHODS: Eligible study participants in this single-center prospective study were patients who routinely used multidose preservative-free saline solution for scleral lens rinsing and filling. Study participants completed a 12-question survey regarding their scleral lens hygiene habits and donated their opened multidose preservative-free saline bottle (PuriLens Plus; The Lifestyle Company, Inc., Freehold, NJ), which was processed for bacterial and fungal cultures. RESULTS: Thirty-five participants (19 males, 16 females) with ages ranging from 6 to 81 years (mean, 47.9 years) were included. Indications for scleral lens wear included those with irregular corneas and ocular surface disease. The overall rate of microbial contamination among saline samples was 62.9% (n = 22). Twenty-one different microorganisms were identified. The survey responses did not differ significantly ( P > .05) for any of the questions with regard to likelihood of positive culture. There were no significant age or sex differences between participants with positive or negative culture results. No significant differences were found between isolation of specific microorganisms and any of the survey responses. CONCLUSIONS: This study suggests that off-label multidose preservative-free saline commonly used to rinse and fill scleral lenses before application on the eye may become contaminated with microorganisms once the bottle has been opened. Eye care practitioners and scleral lens patients should be aware of these potential contaminations and prioritize lens, hand, and environmental hygiene to minimize the risk of ocular complications.